Skin application of 4% menthol enhances running performance in hot and humid climate - Hermand, E.; Collado, A.; Hue, O. (International Journal of Sports Medicine, 2020)
Aerobic performance is negatively impacted by tropical climate due to impairment of thermoregulatory mechanisms. We tested the hypothesis that a torso application of a 4% menthol solution would have the same effect on a best performance 10-km run as an external use of cold water. Thirteen trained male athletes completed four outdoor 10-km runs (T=29.0±1.3°C, relative humidity 59.0±13.6%) wearing a tee-shirt soaked every 2-km either in a cold (~6°C) or warm/ambient (~28°C) solution, consisting in water or in a 4% menthol solution, (CTL, MENT-Amb, CLD and MENT-CLD). Run performances were improved from 4.8 to 6.1% in CLD (51.4±5.5 min), MENT-Amb (52.2±5.9 min) and MENT-CLD (51.4±5.1 min) conditions (vs. CTL, 55.4±8.4 min, P<0.05), without differences between these three conditions, whereas heart rate (177±13bpm), body temperature (38.7±0.6°C) and drink ingestion (356±170?g) were not modified. Thermal sensation after running was lower in MENT-CLD (vs. CTL, P<0.01) and thermal acceptability was higher in CLD and MENT-Amb (vs. CTL, P<0.05), but thermal comfort, feeling scale and rate of perceived exertion remained unchanged. The use of menthol on skin enhances aerobic performance in a tropical climate, and no differences in performance were observed between menthol and traditional percooling strategies. However, combining both menthol and traditional percooling brought no further improvements.